Carbon-coated lithium iron phosphate positive electrode material as well as preparation method and application thereof
By optimizing the heating procedures and process conditions of the high-temperature solid-phase sintering method, the problems of long preparation time and high energy consumption in the existing technology were solved, and carbon-coated lithium iron phosphate positive electrode material with excellent electrochemical performance was obtained, realizing energy consumption Reduce and improve production efficiency.
Patent Information
- Application Number
- CN202411483881.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-23
- Publication Date
- 2025-02-18
AI Technical Summary
The existing carbon-coated lithium iron phosphate positive electrode material preparation method has a long preparation time, high energy consumption, and further improvement in electrochemical performance under high temperature and high pressure conditions.
By designing different heating procedures for high-temperature solid-phase sintering method, the heating section, constant temperature section and cooling section are set, and the carbon coating process conditions are optimized, including increasing temperature of the heating section, controlling the temperature of the constant temperature section between 730℃-850℃, and in the rotary kiln Carbon coating is carried out.
A carbon-coated lithium iron phosphate positive electrode material with excellent electrochemical performance in a short time has been obtained, which reduces energy consumption, improves production efficiency, and achieves better electrochemical performance.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of battery positive electrode material preparation, and specifically relates to a carbon-coated lithium iron phosphate positive electrode material and a preparation method and application thereof. Background Art
[0002] Carbon-coated lithium iron phosphate cathode materials are widely used in pure electric vehicles, energy storage systems and other fields due to their unique properties. Carbon-coated lithium iron phosphate cathode materials occupy an important position in the lithium-ion battery market due to their high safety, long cycle life and low cost.
[0003] At present, the preparation method of carbon-coated lithium iron phosphate positive electrode material mainly includes high-temperature solid phase sintering method, which is a technology for preparing carbon-coated lithium iron phosphate positive electrode material by reaction under extreme conditions such as high temperature and high pressure. This method has the following advantages and is widely used: (1) The equipment and process used in the solid phase sintering method are relatively simple, making the entire preparation process easy to control, which is conducive to industrial production, reducing production costs and improving production efficiency; and it is suitable for large-scale production of carbon-coated lithium iron phosphate positive electrode materials; (2) The raw materials (such as lithium carbonate, iron oxide, iron phosphate, etc.) required for preparing carbon-coated lithium iron phosphate positive electrode materials by this method are widely available and relatively low in cost; (3) In the process of preparing carbon-coated lithium iron phosphate positive electrode materials by this method, no toxic and harmful waste and emissions are generated, which has the advantages of being environmentally friendly and pollution-free, and meets the requirements of sustainable development.
[0004] Therefore, it is necessary to develop a method for preparing carbon-coated lithium iron phosphate positive electrode materials using a high-temperature solid-phase sintering method. Summary of the invention
[0005] The present invention provides a method for preparing a carbon-coated lithium iron phosphate positive electrode material. The method can obtain more carbon-coated lithium iron phosphate positive electrode materials with excellent electrochemical properties in a shorter time by designing different heating procedures of a high-temperature solid-phase sintering method.
[0006] In order to achieve the above object, the present invention can adopt the following technical solutions:
[0007] On the one hand, the present invention provides a method for preparing a carbon-coated lithium iron phosphate positive electrode material, comprising: carbon-coating lithium iron phosphate and a first carbon source to obtain a carbon-coated lithium iron phosphate positive electrode material; the carbon coating process conditions include: setting a heating section, a constant temperature section and a cooling section, wherein the temperature of the heating section increases gradually between 50°C and 750°C; and the temperature of the constant temperature section is 730°C to 850°C.
[0008] Preferably, the above-mentioned carbon coating conditions satisfy one or more combinations of the following conditions: (a) the first carbon source is selected from one or more combinations of glucose, sucrose, starch, citric acid or ascorbic acid; (b) the ratio of lithium iron phosphate to carbon source is 1000:(10-250); (c) the carbon content in the carbon-coated lithium iron phosphate positive electrode material is 1%-2.5%.
[0009] Preferably, the above carbon coating conditions also meet one or more combinations of the following conditions: (a) the heating section is 4-7 sections; (b) the constant temperature section is 3-6 sections; (c) the temperature of the constant temperature section is 780°C-800°C; (d) the time of the heating section is 5h-7h; (e) the time of the constant temperature section is 0.5h-4h; (f) the time of the cooling section is 3h-5h; (g) the carbon coating process is carried out in a rotary kiln; (h) the carbon coating process is carried out in a rotary kiln, and the main drive frequency of the rotary kiln is 10Hz-25Hz; (i) the feeding frequency during the carbon coating process is 5Hz-20Hz; (j) the carbon coating is carried out in a protective gas environment, and the protective gas flow rate is 250m 3 / h-350m 3 / h; (k) oxygen content during carbon coating process is less than 50ppm.
[0010] More preferably, the carbon coating conditions satisfy one or more combinations of the following conditions: (a) there are 6 heating sections; (b) the temperatures of the heating sections are 100°C, 200°C, 300°C, 400°C, 550°C, and 600°C, respectively; (c) there are 3 constant temperature sections; (d) the temperature of the constant temperature section is 780°C; (e) the main drive frequency of the rotary kiln is 18.8 Hz.
[0011] Preferably, the preparation method of the lithium iron phosphate comprises: mixing a lithium source, an iron source, a phosphorus source and a second carbon source, dispersing, spray drying and sintering to obtain a lithium iron phosphate positive electrode material.
[0012] Preferably, the preparation method of the above-mentioned lithium iron phosphate satisfies one or more combinations of the following conditions: (a) the lithium source is selected from one or more combinations of lithium carbonate or lithium hydroxide; (b) the iron source is selected from one or more combinations of ferric oxide, ferrosoferric oxide or ferrous oxide; (c) the phosphorus source is selected from one or more combinations of phosphoric acid, diammonium phosphate or diammonium hydrogen phosphate; (d) the second carbon source is selected from one or more combinations of glucose, sucrose, starch, citric acid, ascorbic acid; (e) the molar ratio of iron:phosphorus in the lithium source, iron source and phosphorus source is 1:1:1; (f) the molar ratio of iron:carbon in the iron source and carbon source is 4:1.
[0013] Preferably, the preparation method of the lithium iron phosphate mentioned above also satisfies one or more combinations of the following conditions: (a) the temperature range of the rotary kiln is 600°C ± 10°C, 700°C ± 10°C, 700°C ± 10°C, 700°C ± 10°C, 700°C ± 10°C, 700°C ± 10°C; (b) the sintering time is 5h-7h; (c) the sintering process is carried out in a rotary kiln; (d) the sintering process is carried out in a rotary kiln, and the main drive frequency of the rotary kiln is 20Hz-25Hz; (d) the feeding frequency of the sintering process is 15Hz-25Hz; (e) the sintering is carried out in a protective gas environment, and the protective gas flow rate is 380m 3 / h-420m 3 / h; (f) oxygen content during sintering is less than 50ppm.
[0014] Another aspect of the present invention provides a carbon-coated lithium iron phosphate positive electrode material, which is prepared by the method for preparing the carbon-coated lithium iron phosphate positive electrode material of the present invention.
[0015] In another aspect, the present invention provides a battery positive electrode sheet, which includes the carbon-coated lithium iron phosphate positive electrode material of the present invention.
[0016] In another aspect, the present invention provides a battery, which includes the battery positive electrode sheet of the present invention.
[0017] The beneficial effects of the present invention include at least:
[0018] (1) The carbon-coated lithium iron phosphate positive electrode material provided by the present invention has excellent electrochemical performance, with a 0.1C gram capacity of 156.57, a 1C gram capacity of 131.61, and a 0.1C efficiency of 96.79%.
[0019] (2) The preparation method of the carbon-coated lithium iron phosphate positive electrode material provided by the present invention uses a rotary kiln for carbon coating, which is more energy-efficient than a roller kiln, as follows: Energy consumption of roller kiln sintering: The length of the kiln heating section and the constant temperature section is 19.25 meters. The energy consumption of the first sintering of lithium iron phosphate material is 1335.1 kWh / ton, and the energy consumption of the second sintering coating carbon is 921.2 kWh / ton; the rotary kiln is in continuous production for 24 hours and 330 days a year, and can achieve an annual output of 4251 tons of carbon-coated lithium iron phosphate material. The production capacity of each conventional roller kiln is 3150 tons / year. The rotary kiln produces 1101 tons more products than the conventional roller kiln each year, and the energy consumption is reduced to 1267.2 kWh / ton, achieving a 5% reduction in energy consumption.
[0020] (3) The preparation method of the carbon-coated lithium iron phosphate positive electrode material provided by the present invention uses a rotary kiln for carbon coating, which has higher production efficiency than a roller kiln, as follows: the rotary kiln can realize continuous production, with a designed production capacity of 1300 kg / h, 31 tons / day, and 10,000 tons / year. Combined with the kiln commissioning results and the product production process requirements, the feed amount and production time are reduced. Under the condition of 24-hour continuous production and 330 days of production per year, the production capacity is 4251 tons / year; while the production capacity of each line of a conventional roller kiln is 3150 tons / year, which is an increase of about 35%.
[0021] (4) The preparation method of the carbon-coated lithium iron phosphate positive electrode material provided by the present invention uses a rotary kiln for carbon coating, which shortens the sintering time compared with a roller kiln; for example, the roller kiln sintering is divided into a heating section, a constant temperature section and a cooling section. The sintering time in the heating section is 1.5 hours, the sintering time in the constant temperature section is 5 hours, and the cooling time in the cooling section is 8 hours, so the total sintering time is 14.5 hours; while the rotary kiln needs to heat up for 6 hours, sinter at a constant temperature for 2.46 hours, and cool for 4 hours, for a total of 12.46 hours; that is, the time is shortened by about 14%. DETAILED DESCRIPTION
[0022] The examples are provided to better illustrate the present invention, but the present invention is not limited to the examples. Therefore, those skilled in the art may make non-essential improvements and adjustments to the implementation scheme according to the above invention content, which still fall within the protection scope of the present invention.
[0023] The terms used herein are only used to describe specific embodiments and are not intended to limit the present disclosure. Unless the context has a significantly different meaning, expressions in the singular include expressions in the plural. As used herein, it should be understood that terms such as "include", "have", "include" are intended to indicate the presence of features, numbers, operations, materials, or combinations. The terms of the present invention are disclosed in the specification, and are not intended to exclude the possibility that one or more other features, numbers, operations, materials, or combinations thereof may exist or may be added. As used herein, " / " may be interpreted as "and" or "or", depending on the circumstances.
[0024] An embodiment of the present invention provides a method for preparing a carbon-coated lithium iron phosphate positive electrode material, comprising: carbon-coating lithium iron phosphate and a first carbon source to obtain a carbon-coated lithium iron phosphate positive electrode material; the carbon coating process conditions include: setting a heating section, a constant temperature section and a cooling section, wherein the temperature of the heating section increases gradually between 50°C and 750°C; and the temperature of the constant temperature section is 730°C to 850°C.
[0025] It should be noted that the carbon coating of lithium iron phosphate in the specific heating stage set in the present invention is shorter and has lower energy consumption than the traditional existing heating stage; and the prepared carbon-coated lithium iron phosphate positive electrode material has good electrochemical properties. In the present invention, it is found that the lithium iron phosphate positive electrode material is first heated incrementally at a temperature of 50°C-750°C, and then heated at a constant temperature of 730°C-850°C and then cooled, which can achieve the purpose of shorter carbon coating time, lower energy consumption, and better performance of the prepared material in the present invention; of course, it should be understood that the incremental heating at a temperature of 50°C-750°C requires more than two heating intervals, and the temperatures of different heating intervals are selected between 50°C-750°C, such as the temperature of the latter temperature interval is greater than the temperature of the previous temperature interval; in addition, the constant temperature heating can be more than one heating interval, and the temperature is 730°C-850°C, such as 750°C, 780°C, 800°C or 830°C.
[0026] In addition, it should be understood that the lithium iron phosphate positive electrode material and the first carbon source need to be dispersed and spray-dried before carbon coating. The operations of dispersion and spray drying are all known in the art. For example, dispersion can be ball milling dispersion. In addition, the lithium iron phosphate positive electrode material in the present invention can be all lithium iron phosphate positive electrode materials known in the art. No matter what method is used to prepare the lithium iron phosphate positive electrode material, it can meet the conditions of this application.
[0027] In some specific examples, the carbon coating conditions may satisfy one or more combinations of the following conditions:
[0028] (a1) the first carbon source is selected from one or more combinations of glucose, sucrose, starch, citric acid or ascorbic acid; specifically, the first carbon source in the present invention includes all carbon-containing substances that can coat the lithium iron phosphate positive electrode material, and one or more combinations of glucose, sucrose, starch, citric acid or ascorbic acid are preferred in the present invention, and the above-mentioned carbon sources have better coating effects;
[0029] (b1) The ratio of lithium iron phosphate to carbon source is 1000:(10-250); for example, 1000:50, 1000:100, 1000:150 or 1000:200, etc.; specifically, the ratio of lithium iron phosphate positive electrode material to carbon content affects the carbon content of the carbon-coated lithium iron phosphate positive electrode material, thereby affecting its charge capacity, initial efficiency, rate performance, etc.;
[0030] (c1) The carbon content in the carbon-coated lithium iron phosphate positive electrode material is 1%-2.5%, preferably 1.5%; specifically, the ratio of the lithium iron phosphate positive electrode material to the carbon content is also a factor affecting the performance of the carbon-coated lithium iron phosphate positive electrode material. The amount of carbon coating determines the conductivity of the lithium iron phosphate, which can indirectly affect the performance such as the charge capacity, the first efficiency, and the rate.
[0031] It should be noted that the above conditions (a1) to (c1) can satisfy one of them, preferably satisfy two of them at the same time; and more preferably satisfy the better condition of satisfying two of them.
[0032] In some specific examples, the above carbon coating conditions also meet one or more combinations of the following conditions:
[0033] (a2) The temperature rise section is 4-7 sections; specifically, as described above, when carbon coating is performed in the present invention, the temperature rise section of the rotary kiln can be set to different sections. In the present invention, it is preferred to set 4-7 sections, such as 5 sections or 6 sections; more preferably, 6 sections; of course, it should be understood that when set to different sections, the temperature also has different setting methods. For example, when it is set to 5 sections, the temperature can be selected in sequence between 100°C and 700°C, such as 100°C, 200°C, 300°C, 400°C, 550°C, etc.; in the present invention, it is more preferred to set 6 sections, and the temperatures are 100°C, 200°C, 300°C, 400°C, 550°C, and 600°C respectively; the carbon coating effect of this temperature rise section is better;
[0034] (b2) the constant temperature section is 3-6 sections; specifically, as described above, the constant temperature section can also be set to different numbers of sections, preferably 3-6 sections, such as 4 sections or 5 sections, among which 3 sections are preferred; the carbon coating effect is better;
[0035] (c2) the temperature of the constant temperature section is 780°C-800°C; specifically, the temperature of the constant temperature section may preferably be 780°C-800°C, such as 790°C, and more preferably 780°C in the present invention, at which the carbon coating effect is better;
[0036] (d2) The time of the heating stage can be 5h-7h, such as 5.5h, 6h or 6.5h;
[0037] (e2) The time of the constant temperature section is 0.5h-4h, such as 1h, 1.5h, 2h, 2.5h, 3h or 3.5h;
[0038] (f2) The cooling period is 3h-5h, such as 3.5h, 4h or 4.5h;
[0039] (g2) The carbon coating process is carried out in a rotary kiln; specifically, the carbon coating process is carried out in a rotary kiln, and heat transfer is more uniform;
[0040] (h2) The carbon coating process is carried out in a rotary kiln, and the main drive frequency of the rotary kiln can be 10 Hz-25 Hz; specifically, the setting of the main drive frequency of the rotary kiln affects the contact between the positive electrode material and the first carbon source, thereby affecting the efficiency of the carbon coating reaction. In the present invention, 10 Hz-25 Hz is preferred, such as 13 Hz, 15 Hz, 18 Hz, 20 Hz, 22 Hz or 25 Hz, etc.; more preferably 18.8 Hz, the main drive frequency has a better carbon coating effect;
[0041] (i2) The feeding frequency of the carbon coating process is 5 Hz-20 Hz, such as 8 Hz, 12 Hz, 15 Hz, 18 Hz or 19 Hz;
[0042] (j2) Carbon coating was carried out in a protective gas environment with a protective gas flow rate of 250m 3 / h-350m 3 / h; Specifically, in order to reduce the side reactions during the carbon coating reaction, the carbon coating process is carried out in a protective gas environment. The protective gas is a gas known in the art, such as nitrogen, helium or argon, which can be selected according to the specific situation; the protective gas flow rate can be 250m 3 / h-350m 3 / h, for example 270m 3 / h、300m 3 / h or 320m 3 / h, etc.
[0043] (k2) The oxygen content during the carbon coating process is less than 50 ppm; specifically, as mentioned above, in order to reduce side reactions during the carbon coating reaction, the carbon coating process is carried out in an oxygen-free environment, that is, the oxygen content is less than 50 ppm.
[0044] It should be noted that in the preparation method of the carbon-coated lithium iron phosphate positive electrode material in the present invention, the preparation conditions can satisfy any one of the conditions (a1) to (c1) and (a2) to (k2), and can satisfy two or more conditions at the same time, preferably satisfy two or more conditions at the same time, more preferably satisfy all conditions at the same time; and more preferably, satisfy the optimal conditions of all conditions at the same time.
[0045] In some specific examples, the preparation method of the lithium iron phosphate includes: mixing a lithium source, an iron source, a phosphorus source and a second carbon source, dispersing, spray drying, and sintering to obtain the lithium iron phosphate.
[0046] It should be noted that, as described above, the lithium iron phosphate in the present invention can be lithium iron phosphate prepared by any preparation method known in the art; in addition, it should be understood that the above-mentioned mixing, dispersion, and spray drying are all conventional operations known in the art, such as dispersion can be achieved by ball milling.
[0047] In some specific examples, the preparation method of lithium iron phosphate satisfies one or more combinations of the following conditions:
[0048] (a3) the lithium source is selected from one or more combinations of lithium carbonate or lithium hydroxide; specifically, the lithium source includes all lithium sources known in the art, preferably commonly used lithium carbonate or lithium hydroxide or a combination thereof;
[0049] (b3) the iron source is selected from one or more combinations of ferric oxide, ferrosoferric oxide or ferrous oxide; specifically, the iron source includes all iron sources known in the art, preferably one or more combinations of ferric oxide, ferrosoferric oxide or ferrous oxide that are commonly used and have good effects;
[0050] (c3) the phosphorus source is selected from one or more combinations of phosphoric acid, ammonium dihydrogen phosphate or diammonium hydrogen phosphate; specifically, the phosphorus source includes all phosphorus sources known in the art, preferably one or more combinations of phosphoric acid, ammonium dihydrogen phosphate or diammonium hydrogen phosphate with good commonly used effects;
[0051] (d3) the second carbon source is selected from one or more combinations of glucose, sucrose, starch, citric acid, and ascorbic acid; specifically, the second carbon source includes all carbon sources known in the art, preferably one or more combinations of glucose, sucrose, starch, citric acid, and ascorbic acid that are commonly used and have good effects;
[0052] (e3) the molar ratio of iron:phosphorus in the lithium source, iron source and phosphorus source is 1:1:1; specifically, in the preparation of lithium iron phosphate, the molar ratio of iron:phosphorus in the lithium source, iron source and phosphorus source is preferably 1:1:1; the prepared lithium iron phosphate and the prepared carbon-coated lithium iron phosphate positive electrode material have better performance;
[0053] (f3) The molar ratio of iron to carbon in the iron source and the carbon source is 4:1; specifically, in the preparation of lithium iron phosphate, the molar ratio of iron to carbon in the iron source and the carbon source is preferably 4:1; the prepared lithium iron phosphate and the prepared carbon-coated lithium iron phosphate positive electrode materials have better performance.
[0054] It should be noted that in the preparation method of the carbon-coated lithium iron phosphate positive electrode material in the present invention, the preparation conditions can satisfy any one of the conditions (a1) to (c1), (a2) to (k2) and (a3) to (f3), and can satisfy two or more conditions at the same time, preferably satisfy two or more conditions at the same time, more preferably satisfy all conditions at the same time; and more preferably, satisfy the optimal conditions of all conditions at the same time.
[0055] In some specific examples, the preparation method of the lithium iron phosphate positive electrode material further satisfies one or more combinations of the following conditions:
[0056] (a4) the temperature range of the rotary kiln is 600°C ± 10°C, 700°C ± 10°C, 700°C ± 10°C, 700°C ± 10°C, 700°C ± 10°C, 700°C ± 10°C; specifically, the temperature range of the rotary kiln can be set arbitrarily, and the above temperature range is preferred, and the performance of the prepared lithium iron phosphate positive electrode material is better;
[0057] (b4) Sintering time is 5h-7h, such as 5.5h, 6h or 6.5h;
[0058] (c4) The sintering process is carried out in a rotary kiln; specifically, the carbon coating process is carried out in a rotary kiln, and the heat transfer is more uniform;
[0059] (d4) The sintering process is carried out in a rotary kiln, and the main drive frequency of the rotary kiln is 20 Hz-25 Hz, such as 22 Hz, 23 Hz or 24 Hz;
[0060] (e4) The feeding frequency of the sintering process is 15Hz-25Hz, such as 17Hz, 19Hz, 21Hz or 23Hz;
[0061] (f4) Sintering is carried out in a protective gas environment with a protective gas flow rate of 380m 3 / h-420m 3 / h; Specifically, in order to reduce the side reactions during the sintering reaction, the sintering process is carried out in a protective gas environment. The protective gas is a gas known in the art, such as nitrogen, helium or argon, which can be selected according to the specific situation; the protective gas flow rate can be 380m 3 / h-420m 3 / h, for example 400m 3 / h、410m 3 / h or 415m 3 / h, etc.
[0062] (g4) The oxygen content during the sintering process is less than 50 ppm; specifically, as mentioned above, in order to reduce side reactions during the sintering reaction, the sintering process is carried out in an oxygen-free environment, that is, the oxygen content is less than 50 ppm.
[0063] It should be noted that in the preparation method of the carbon-coated lithium iron phosphate positive electrode material in the present invention, the preparation conditions can satisfy any one of the conditions (a1) to (c1), (a2) to (k2), (a3) to (f3) and (a4) to (g4), and can satisfy two or more conditions at the same time, preferably satisfy two or more conditions at the same time, more preferably satisfy all conditions at the same time; and more preferably, satisfy the optimal conditions of all conditions at the same time.
[0064] It should also be noted that the preparation method of the carbon-coated lithium iron phosphate positive electrode material in the present invention can adopt a roller kiln or a rotary kiln; specifically, the heating zone of the roller kiln is composed of 11 temperature zones, which are respectively powered by multiple groups of AC contactors, so that the instantaneous current impact of the equipment on the power grid can be reduced, and the equipment can respectively detect and control the left, middle and right three areas of the furnace width, and by adjusting the set temperature of each area and the upper and lower heating output ratio, the uniformity of the effective space of the furnace is ensured to be less than ±3°C; however, graphite bowls are required to be used to load materials, and the graphite bowls need to be manually loaded and inverted. The materials are stationary, and the graphite bowls are driven forward by rolling with a stick. The heat transfer during sintering is slow, the sintering time is long, and the temperature distribution is uneven, resulting in uneven particles of the synthesized lithium iron phosphate product, which is amorphous and has a long synthesis time; and the rotary kiln adopts multi-temperature zone independent temperature control heating, and each temperature zone is arranged in a unified heating furnace body. The temperature of each temperature zone can be independently adjusted according to the product process requirements, and the process adaptability is strong. The heating furnace body insulation materials are all made of low thermal conductivity, low heat storage and high temperature ceramic fiber materials, which greatly improves the insulation effect and significantly saves energy when the equipment is in operation; therefore, the present invention preferably uses a rotary kiln for preparation.
[0065] In addition, when the roller kiln sintered the positive electrode material, a graphite bowl was used to hold the material. The material was stationary, and the graphite bowl was driven forward by the rolling of the stick. The heat transfer during sintering was slow, the sintering time was long, and the temperature distribution was uneven, resulting in uneven particles of the synthesized lithium iron phosphate product, which was amorphous and took a long time to synthesize. The long and complicated process of repeated grinding and calcination resulted in the formation of larger particles with lower electrochemical performance. In addition, in the cooling stage, the material outside cooled first, but the material inside had difficulty in dissipating heat, and more time was required for heat dissipation, resulting in a long sintering time. The use of a rotary kiln for sintering can overcome the above-mentioned defects, so a rotary kiln is preferably used for preparation in the present invention.
[0066] The present invention also provides a carbon-coated lithium iron phosphate positive electrode material, which is prepared by the preparation method of the carbon-coated lithium iron phosphate positive electrode material of the present invention.
[0067] It should be noted that the carbon-coated lithium iron phosphate positive electrode material prepared by the preparation method of the present invention has excellent electrochemical properties, and its 0.1C efficiency can reach 96.79%; in addition, the carbon content in the carbon-coated lithium iron phosphate positive electrode material is preferably 1%-2.5% in the present invention; it should be understood that the present invention controls the carbon content in the carbon-coated lithium iron phosphate positive electrode material by adding the first carbon source. The carbon content of carbon sources such as glucose, sucrose, and polyacrylonitrile is different, and the amount added will be different.
[0068] An embodiment of the present invention further provides a battery positive electrode sheet, which includes the carbon-coated lithium iron phosphate positive electrode material of the present invention.
[0069] It should be noted that, as described above, the carbon-coated lithium iron phosphate positive electrode material in the present invention has excellent electrochemical properties, and can be prepared into a battery positive electrode sheet by combining it with materials such as a conductive agent, a binder and a current collector (such as aluminum foil); in addition, the conductive agent, the binder and the current collector are all materials known in the art.
[0070] An embodiment of the present invention further provides a battery, which includes the battery positive electrode sheet of the present invention.
[0071] It should be noted that, based on the excellent electrochemical properties of the carbon-coated lithium iron phosphate positive electrode material in the present invention, the battery positive electrode sheet prepared therefrom can be assembled into a lithium iron phosphate battery; of course, it should be understood that the lithium iron phosphate battery also includes other components, such as an electrolyte, a negative electrode, a diaphragm or a battery shell, etc.; the electrolyte, the negative electrode, the diaphragm or the battery shell are all materials known in the art.
[0072] In order to better understand the present invention, the content of the present invention is further explained below in conjunction with specific examples, but the content of the present invention is not limited to the following examples.
[0073] 1. Sample preparation
[0074] Example 1
[0075] (1) mixing a lithium source, an iron source and a phosphorus source in a lithium: iron: phosphorus molar ratio of 1:1:1; and an iron: carbon molar ratio of 4:1 to obtain a mixture, then adding the mixture into water, keeping the solid content at 50%, and performing a wet ball milling (using two-stage ball milling, first coarse grinding and then fine grinding, coarse grinding using zirconia balls with a diameter of 1.0 mm-1.2 mm, a rotation speed of 800 rpm / min, and a coarse grinding time of 1 h; fine grinding using zirconia balls with a diameter of 0.6 mm-0.8 mm, a rotation speed of 800 rpm / min, and a fine grinding time of 1 h) to obtain a slurry;
[0076] (2) spray drying the slurry and transferring it into a rotary kiln for the first sintering to obtain lithium iron phosphate powder.
[0077] (3) subjecting the lithium iron phosphate obtained by the first sintering to ball milling spray drying and then to a second sintering;
[0078] (4) The solid after the second sintering is subjected to air flow crushing to obtain carbon-coated lithium iron phosphate powder;
[0079] The sintering conditions for the first sintering and the second sintering are shown in Table 1 and Table 2 respectively;
[0080] Table 1 First sintering conditions of Example 1
[0081] Sintering conditions parameter Feeding frequency 20Hz Main drive frequency 22Hz Nitrogen flow <![CDATA[400m 3 / h]]> Oxygen content <50ppm Kiln temperature range 600℃、700℃、700℃、700℃、700℃、700℃ Total sintering time 6h (1h for each zone temperature)
[0082] Table 2 Second sintering conditions of Example 1
[0083]
[0084] Example 2
[0085] The difference between Example 2 and Example 1 is that the sintering conditions of the second sintering in Example 2 are different from those in Example 1. The sintering conditions of the second sintering in Example 2 are shown in Table 3 below, and the rest are the same as in Example 1.
[0086] Table 3 Second sintering conditions of Example 2
[0087]
[0088] Example 3
[0089] The difference between Example 3 and Example 1 is that the sintering conditions of the second sintering in Example 3 are different from those in Example 1. The sintering conditions of the second sintering in Example 3 are shown in Table 4 below, and the rest are the same as in Example 1.
[0090] Table 4 Second sintering conditions of Example 3
[0091]
[0092] Example 4
[0093] The difference between Example 4 and Example 1 is that the sintering conditions of the second sintering in Example 4 are different from those in Example 1. The sintering conditions of the second sintering in Example 4 are shown in Table 5 below, and the rest are the same as in Example 1.
[0094] Table 5 Second sintering conditions of Example 4
[0095]
[0096]
[0097] Example 5
[0098] The difference between Example 5 and Example 1 is that the sintering conditions of the second sintering in Example 5 are different from those in Example 1. The sintering conditions of the second sintering in Example 5 are shown in Table 6 below, and the rest are the same as in Example 1.
[0099] Table 6 Second sintering conditions of Example 5
[0100]
[0101] Example 6
[0102] The difference between Example 6 and Example 1 is that the sintering conditions of the second sintering in Example 6 are different from those in Example 1. The sintering conditions of the second sintering in Example 6 are shown in Table 7 below, and the rest are the same as in Example 1.
[0103] Table 7 Second sintering conditions of Example 6
[0104]
[0105]
[0106] Example 7
[0107] The difference between Example 7 and Example 1 is that the sintering conditions of the second sintering in Example 7 are different from those in Example 1. The sintering conditions of the second sintering in Example 7 are shown in Table 8 below, and the rest are the same as in Example 1.
[0108] Table 8 Second sintering conditions of Example 7
[0109]
[0110] Example 8
[0111] The difference between Example 8 and Example 1 is that the sintering conditions of the second sintering in Example 6 are different from those in Example 1, and the sintering conditions of the second sintering in Example 8 are shown in Table 9 below, and the rest are the same as in Example 1.
[0112] Table 9 Second sintering conditions of Example 8
[0113]
[0114] Example 9
[0115] The difference between Example 9 and Example 1 is that the sintering conditions for the second sintering in Example 9 are different from those in Example 1. The sintering conditions for the second sintering in Example 9 are shown in Table 10 below, and the rest are the same as in Example 1.
[0116] Table 10 Second sintering conditions of Example 9
[0117]
[0118]
[0119] Comparative Example 1
[0120] The difference between Comparative Example 1 and Example 1 is that the first sintering conditions and the second sintering conditions in the comparative example are different from those in Example 1. The first sintering conditions and the second sintering conditions in the comparative example 1 are shown in Tables 11 and 12 below, respectively, and the rest are the same as Example 1.
[0121] Table 11 Comparative Example 1 First Sintering Conditions
[0122]
[0123] Table 12 Second sintering conditions of comparative example 1
[0124]
[0125]
[0126] Comparative Example 2
[0127] The difference between Comparative Example 2 and Comparative Example 1 is that the sintering conditions of the second sintering in Comparative Example 2 are different from those in Comparative Example 1. The sintering conditions of the second sintering in Comparative Example 2 are shown in Table 13 below, and the rest are the same as Comparative Example 1.
[0128] Table 13 Second sintering conditions of comparative example 2
[0129]
[0130] Comparative Example 3
[0131] The difference between Comparative Example 2 and Comparative Example 1 is that the sintering conditions of the second sintering in Comparative Example 2 are different from those in Comparative Example 1. The sintering conditions of the second sintering in Comparative Example 2 are shown in Table 14 below, and the rest are the same as Comparative Example 1.
[0132] Table 14 Second sintering conditions of comparative example 3
[0133]
[0134]
[0135] Comparative Example 4
[0136] Carbon coating is carried out using a roller kiln as follows:
[0137] When lithium iron phosphate is synthesized once, the temperature is 100°C, 200°C, 300°C, 500°C, and 700°C in the heating sections 1-5 (the total time is 1.5 hours, and the time in each section is evenly distributed), and the temperature is 700°C, 700°C, 700°C, 700°C, 700°C, 700°C, and 700°C in the constant temperature sections 6-11 (the total time is 3 hours, and the time in each section is evenly distributed). After the constant temperature is completed, the heating is turned off and the cooling is carried out by purging with nitrogen for 8.5 hours;
[0138] During the secondary lithium iron phosphate carbon coating, the temperatures in the heating sections 1-8 (total time is 1.5 hours, and the time in each section is evenly distributed) are 100°C, 200°C, 300°C, 400°C, 500°C, 550°C, 600°C, and 700°C; the temperatures in the constant temperature sections 9-15 (total time is 5 hours, and the time in each section is evenly distributed) are 780°C, 780°C, 780°C, 780°C, 780°C, 780°C, and 780°C; after the constant temperature is completed, the heating is turned off and the solid is cooled for 8 hours by purging with nitrogen; the cooled solid is crushed by air flow to obtain carbon-coated lithium iron phosphate powder.
[0139] 2. Sample testing
[0140] The carbon-coated lithium iron phosphate powders prepared in Examples 1 to 9 and Comparative Examples 1 to 3 were prepared into electrode sheets and button cells (preparation of electrode sheets and button cells: carbon-coated lithium iron phosphate powder: SP: PVDF were added into a degassing tank in a mass ratio of 90:5:5, degassed and stirred into a uniform slurry, the slurry was evenly coated on aluminum foil with a coater, dried in a vacuum drying oven at 90°C for 16 hours, cut and assembled into CR2016 type button cells in a glove box) to test their electrochemical properties. The LiFePO4 / / Li body was tested at room temperature using a blue battery test system. The system performs constant current charge and discharge test, and the test voltage range is 2V-3.75V; the specific process is: standing for 6h - constant current charging (0.1C) until the voltage reaches 3.75V - constant voltage charging, until the current reaches 0.02C or the charging time exceeds half an hour - standing for 5min - constant current discharge (0.1C) until the voltage reaches 2V - standing for 5min - constant current charging (1C) until the voltage reaches 3.75V - constant voltage charging, until the current reaches 0.02C or the charging time exceeds half an hour - constant current discharge (1C) until the voltage reaches 2V - standing for 5min - test ends, and the test results are shown in Table 15 below.
[0141] Table 15 Electrochemical properties of lithium iron phosphate powders prepared in Examples and Comparative Examples
[0142]
[0143] As shown in Table 15 above, the comprehensive effects of Example 1, Example 8 and Example 9 are better, all better than Comparative Examples 1 to 4, indicating that the electrochemical performance of the carbon-coated lithium iron phosphate positive electrode material prepared by the sintering method of the present invention is better than the existing heating method.
[0144] In addition, the crystal structure and lithium ion migration rate of the lithium iron phosphate powder prepared in Example 1, Example 8, Example 9 and Comparative Examples 1 to 4 were also tested, and the results are shown in Table 16 below.
[0145] XRD (X-ray diffraction) test, under CuKa radiation ( The X-ray diffraction (XRD) patterns were recorded at 60 kV, 60 mA, and the unit cell parameters were obtained after XRD refinement.
[0146] The carbon content of the finished lithium iron phosphate product is tested by an infrared carbon analyzer. The sample weight is 0.2±0.01g, and tungsten flux particles and pure iron flux are added before testing.
[0147] The lithium ion migration rate is obtained by testing the electrochemical impedance spectroscopy (EIS) of the button battery and fitting the data; the lithium chemical diffusion coefficient can be calculated by formulas (1) and (2).
[0148] Z'=σ*ω -0.5 (1)
[0149]
[0150] Where Z' is the Warburg impedance, σ is the Warburg impedance factor, and ω is the angular frequency (2πf). σ can be obtained from Z' and ω in the EIS data. -0.5 It can be obtained by formula (1); then substituting σ into formula (2) to obtain D Li+ In formula (2), R represents the gas constant (R = 8.314 Jmol / K), T represents the absolute temperature of the test environment, A represents the area of the positive electrode material immersed in the electrolyte, n represents the number of electrons in the electrochemical reaction (n = 2), F is the Faraday constant (F = 96500 C / mol), C Li is the molar concentration of lithium ions.
[0151] Table 16 Crystal structure and lithium ion migration rate of lithium iron phosphate powder prepared in Examples 1, 8 and 9 and Comparative Example
[0152]
[0153] It can be seen from the above table that the lithium ion migration rates of the lithium iron phosphate in the embodiment and the comparative example are of the same order of magnitude, but the constant temperature time of the rotary kiln (the heating method of the present invention) is less than that of the roller kiln (the existing heating method), which can shorten the sintering time and achieve energy saving and efficiency improvement. In addition, the secondary sintering temperature and time will affect the crystal structure of lithium iron phosphate, and the increase in a, c lattice constants is attributed to the carbon coating. During the calcination process, the carbon layer coated on the surface reacts with oxygen to produce some oxygen vacancies, which is beneficial to improve the electrochemical properties of the electrode material.
[0154] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the purpose and scope of the technical solution of the present invention, which should be covered by the scope of the claims of the present invention.
Claims
1. A method for preparing a carbon-coated lithium iron phosphate positive electrode material, characterized in that: include: Carbon-coated lithium iron phosphate and a first carbon source are prepared to obtain a carbon-coated lithium iron phosphate positive electrode material; The carbon coating process conditions include: setting a temperature rising section, a constant temperature section and a temperature falling section, wherein the temperature of the temperature rising section increases gradually from 50°C to 750°C; the temperature of the constant temperature section is 730°C to 850°C.
2. The preparation method according to claim 1, characterized in that: The carbon coating conditions meet one or more of the following conditions: (a) the first carbon source is selected from one or more combinations of glucose, sucrose, starch, citric acid or ascorbic acid; (b) The ratio of lithium iron phosphate to carbon source is 1000:(10-250); (c) The carbon content in the carbon-coated lithium iron phosphate positive electrode material is 1%-2.5%.
3. The preparation method according to claim 1 or 2, characterized in that: The carbon coating conditions meet one or more of the following conditions: (a) The heating stage is 4-7 stages, (b) Constant temperature section is 3-6; (c) The temperature of the constant temperature section is 780°C-800°C; (d) The heating period is 5h-7h; (e) The time of the constant temperature section is 0.5h-4h; (f) The cooling period is 3h-5h; (g) The carbon coating process is carried out in a rotary kiln; (h) The carbon coating process is carried out in a rotary kiln, and the main drive frequency of the rotary kiln is 10Hz-25Hz; (i) The feeding frequency of the carbon coating process is 5Hz-20Hz; (j) Carbon coating was carried out in a protective gas environment with a protective gas flow rate of 250m 3 / h-350m 3 / h; (k) The oxygen content during carbon coating is less than 50 ppm.
4. The preparation method according to claim 3, characterized in that: The carbon coating conditions meet one or more of the following conditions: (a) The heating stage is 6 stages. (b) The temperatures in the heating stage are 100°C, 200°C, 300°C, 400°C, 550°C, and 600°C respectively; (c) There are 3 constant temperature sections; (d) The temperature of the constant temperature section is 780°C; (e) The main drive frequency of the rotary kiln is 18.8 Hz.
5. The preparation method according to claim 3, characterized in that: The preparation method of lithium iron phosphate comprises: mixing a lithium source, an iron source, a phosphorus source and a second carbon source, dispersing, spray drying and sintering to obtain lithium iron phosphate.
6. The preparation method according to claim 5, characterized in that: The preparation method of lithium iron phosphate meets one or more of the following conditions: (a) the lithium source is selected from one or more combinations of lithium carbonate and lithium hydroxide; (b) the iron source is selected from one or more combinations of ferric oxide, ferrosoferric oxide or ferrous oxide; (c) the phosphorus source is selected from one or more combinations of phosphoric acid, ammonium dihydrogen phosphate or diammonium hydrogen phosphate; (d) the second carbon source is selected from one or more combinations of glucose, sucrose, starch, citric acid, and ascorbic acid; (e) the molar ratio of iron to phosphorus in the lithium source, the iron source and the phosphorus source is 1:1:1; (f) The molar ratio of iron to carbon in the iron source and the carbon source is 4:
1.
7. The preparation method according to claim 5 or 6, characterized in that: Sintering meets one or more of the following conditions: (a) The temperature range of the rotary kiln is 600℃±10℃, 700℃±10℃, 700℃±10℃, 700℃±10℃, 700℃±10℃, 700℃±10℃, 700℃±10℃; (b) sintering time is 5h-7h; (c) the sintering process is carried out in a rotary kiln; (d) The sintering process is carried out in a rotary kiln, and the main drive frequency of the rotary kiln is 20Hz-25Hz; (e) The feeding frequency of the sintering process is 15Hz-25Hz; (f) Sintering is carried out in a protective gas environment with a protective gas flow rate of 380m 3 / h-420m 3 / h; (g) The oxygen content during sintering is less than 50 ppm.
8. Carbon-coated lithium iron phosphate positive electrode material, characterized in that: The compound is prepared by the preparation method according to any one of claims 1 to 7.
9. A positive electrode sheet for a battery, characterized in that: Including the carbon-coated lithium iron phosphate positive electrode material as described in claim 8.
10. A battery, characterized in that Including the battery positive electrode sheet as described in claim 9.
Citation Information
Cited By
Lithium iron phosphate positive electrode material and preparation method thereof
CN120004236A
Lithium iron phosphate cathode material and its preparation method
CN120004236B